Unions, social media and young workers—evidence from the UK. (14th November 2019) - Hodder, Andy; Houghton, David J.
Abstract : This paper explores the way in which the youth sections of three British unions use social media. We contribute to both the literature on unions and young workers, and union engagement with social media by providing the first systematic examinations of union youth sections' social media usage in terms of method, scope and content. The paper examines differences in Twitter usage between the youth sections of GMB, PCS and Unite over a two‐year period from June 1, 2014, to May 31, 2016. The paper considers the extent to which these union accounts fully utilise the interactive capabilities of social media, and whether the content of messages is specifically targeted towards young workers. We find similarities between the three accounts in terms of message content and focus and that the youth sections of unions are more involved with the interactive capabilities of Web 2.0 than the existing literature suggests.